Pengaruh Good Governance dan Tingkat Kemandirian Keuangan Daerah terhadap Kinerja Pemerintah Daerah Kabupaten/Kota Lampung tahun 2018 - 2022 - Roza, Elfira; Arza, Fefri Indra (Universitas Negeri Padang, 2025)
This study aims to obtain empirical evidence and examine the influence of good governance and regional financial independence on local government performance. The population in study consist of all regencies and cities in lampung Province, with a sample of 15 regencies/cities in Lampung Province during the 2018-2022 period. The sampling technique used is saturated sampling, resulting in a total of 75 samples. This researches is a causal study with a quantitative approach. The data used in this study is secondary data. Data analysis was conducted using multiple linear regression analysis. The results of the study indicate that good governance significantly affects logal government performance.